Studi agrobiofisik kamandrah (croton tiglium L.) dan penentuan potensi awal kamandrah sebagai larvasida hayati pencegah penyakit demam berdarah dengue - Dyah Iswantini; Rosihan Rosman; Upik Kesumawati; Djumali Mangunwidjaja; Min Rahminiwati; Adi Riyadhi (Institut Pertanian Bogor, 2009)
The aim of the research is to obtain the ecological condition and propagation of kamandrah (Croton tiglium L.) and determination of its potency as biological larvacidal for preventing dengue haemorraghic fever. Agrobiophysic study indicated that Croton tiglium L. plant need full sunlight(> 70 %). low intensity of sunlight could decrease the ability of plant to produce seed. The plant could grow well on podzolic land (30-50 m upon sea surface). Seed of kamandrah from Ampah has growth percentage of 43.8 °/o, height of 27.5 em, stem diameter of 5 em, total leaves of 10, and total primary branches of 2. Phytochemical assay resulted that among other part of Kamandrah, Kamandrah seed has highest alkaloid content. Because alkaloid compound has high larvicidal activity, kamandrah seed has high potency as larvicide. Among all of extracts of part of plant, oil of Croton tiglium L. has the highest potency as biological larvacidal with 863.67 ppm of LC50 for 24 hours of treatment.